1997
DOI: 10.1161/01.str.28.6.1158
|View full text |Cite
|
Sign up to set email alerts
|

Silent Brain Infarction on Magnetic Resonance Imaging and Neurological Abnormalities in Community-Dwelling Older Adults

Abstract: MRI evidence of brain infarction is common in older men and women without a clinical history of stroke. Their strong associations with impaired cognition and neurological deficits suggest that they are neither silent nor innocuous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
215
2
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(240 citation statements)
references
References 25 publications
18
215
2
4
Order By: Relevance
“…MRI infarcts and infarct-like lesions were classified without reference to clinical signs or symptoms; their relationship to symptoms and clinically recognized stroke has been reported previously. 12 Cerebral ventricular size was assessed on a scale of 0 to 9 by comparison with a series of 8 studies with successively increasing ventricular size ranging from small (grade 1) to severe enlargement (grade 8). Studies considered to have ventricles smaller than those in grade 1 received grade 0, and worse than grade 8 received grade 9.…”
Section: Cerebral Mrimentioning
confidence: 99%
“…MRI infarcts and infarct-like lesions were classified without reference to clinical signs or symptoms; their relationship to symptoms and clinically recognized stroke has been reported previously. 12 Cerebral ventricular size was assessed on a scale of 0 to 9 by comparison with a series of 8 studies with successively increasing ventricular size ranging from small (grade 1) to severe enlargement (grade 8). Studies considered to have ventricles smaller than those in grade 1 received grade 0, and worse than grade 8 received grade 9.…”
Section: Cerebral Mrimentioning
confidence: 99%
“…White matter lesions (WMLs) have been reported to be a predictive factor in vascular dementia [1][2][3][4] and stroke, [5][6][7] and are generally regarded as chronic ischemic lesions of the brain. Prior attempts to attribute their cause to general arteriosclerosis have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the male predominance of silent brain infarction (SBI) was inconsistent in the earlier studies. [7][8][9][10][11] With regard to SBI, the North Manhattan Study found that male sex was independently associated with SBI on a multivariable logistic regression model. 7 Although the Rotterdam Scan Study reported a higher prevalence of SBI among women than men, the sex difference was no longer statistically significant when adjusted for other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, sex was not independently associated with an increased risk of SBI in the Cardiovascular Health Study and Framingham Offspring Study. 10,11 In this study, we conducted a population-based, cross-sectional analysis of brain MRI findings to examine the relationship between sex differences in the risk profile and SBI.…”
Section: Introductionmentioning
confidence: 99%